2007
DOI: 10.1113/expphysiol.2006.035253
|View full text |Cite
|
Sign up to set email alerts
|

Roux‐en‐Y or ‘uncut’ Roux procedure? Relation of intestinal migrating motor complex recovery to the preservation of the network of interstitial cells of Cajal in pigs

Abstract: We designed a conscious pig model to investigate myoelectric activity and the number of interstitial cells of Cajal (ICC) in the proximal jejunum following the Roux-en-Y and 'uncut' Roux procedures in relation to clinical outcomes. Twelve male Polish White pigs (8 weeks old, 10-13 kg) underwent surgery under general anaesthesia first to implant bipolar electrodes and telemetry transmitters for continuous electromyography recordings and then, after 1 week recovery, to create Roux-en-Y (n = 6) and 'uncut' Roux l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The authors concluded that the "uncut procedure" may lessen the effects on migrating motor complex, decreasing the impairment of gastrointestinal motility and remarkably increasing the expression of c-kit mRNA related to the presence of interstitial cells of Cajal 17 . In another study, the number of Cajal cells in the region of Auerbach´s plexus was higher in "uncut" animals when compared with "cut" Roux limb, and they concluded that this fact was important to the preservation of intestinal motility 18 . The effects of Roux-en-Y or jejunal interposition after total gastrectomy in rats were evaluated concluding that the jejunal interposition induced fewer disturbances on intestinal transit and nutrition status of the rats than those of Roux procedure 19. A study with 234 adult subjects, submitted to Rouxgastrectomy concluded that patients presenting gastric stasis symptoms had long Roux-en-Y limbs of 41 cm of average length; moreover, it suggested that the curtailment of such limbs must be done in order to improve the symptoms 8 .…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that the "uncut procedure" may lessen the effects on migrating motor complex, decreasing the impairment of gastrointestinal motility and remarkably increasing the expression of c-kit mRNA related to the presence of interstitial cells of Cajal 17 . In another study, the number of Cajal cells in the region of Auerbach´s plexus was higher in "uncut" animals when compared with "cut" Roux limb, and they concluded that this fact was important to the preservation of intestinal motility 18 . The effects of Roux-en-Y or jejunal interposition after total gastrectomy in rats were evaluated concluding that the jejunal interposition induced fewer disturbances on intestinal transit and nutrition status of the rats than those of Roux procedure 19. A study with 234 adult subjects, submitted to Rouxgastrectomy concluded that patients presenting gastric stasis symptoms had long Roux-en-Y limbs of 41 cm of average length; moreover, it suggested that the curtailment of such limbs must be done in order to improve the symptoms 8 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, effects of surgical techniques in the GIT on intestinal motility were studied in a pig model and could explain the difference in recovery in patients (75) . Besides the large size of adult pigs, anatomical similarities to the human GIT and pancreas and similar dietary requirements make this species amenable for studying human-sized equipment and developing new techniques in pancreatic surgery.…”
Section: Swine As a Model Of The Human Speciesmentioning
confidence: 99%
“…We hypothesized that this modified technique had three advantages over conventional Roux-en-Y hepaticojejunostomy. First, the modified biliary-enteric anastomosis can be performed without transection of the jejunum; it thus avoids separation of the duodenal pacemaker from the jejunum, maintains the integrity of the jejunum, and allows normal conduction of myenteric impulses [12]. Huang et al have proved that the silk suture placed across the jejunal wall in the modified Warren operation does not disrupt myoelectrical continuity in the uncut bile duct-enteric loop in rabbits.…”
Section: Discussionmentioning
confidence: 99%